Development of a mobile application for assessing reaction time in walking and TUG duration: Concurrent validity in female older adults - Pumpho, Ampha; Kaewsanmung, Supapon; Keawduangdee, Petcharat; Suwannarat, Patcharawan; Boonsinsukh, Rumpa (Frontiers in Medicine, 2023)
Introduction: The TUG test was demonstrated to be able to discriminate fallers from non-fallers. Also, the TUG-dual was commonly used to assess cognitive dual-task performance while walking for fall prediction. To provide more convenience for recording walking duration, recent research has developed a mobile application that allows easy interaction with the user to record the duration of a single task (walking test or TUG test), dual-task (walking or TUG with the cognitive task), and reaction time assessment. Objective: The purpose of our study was to determine the concurrent validity of the mobile application that was developed for the clinical assessment of TUG, TUG-subtraction, and reaction time. Methods: A total of 30 older adults participated in this study. The testing protocol involved the TUG, TUG-subtraction, and reaction time assessment. For TUG and TUG-subtraction, the duration to complete the task was recorded by the APDM Mobility Lab system and the mobile application. For the reaction time tests, the reaction times (msec) were recorded by the Multi Choice Reaction timer and the Mobile application. For the concurrent validity, TUG durations by the APDM Mobility Lab system were correlated with the mobile application to establish the concurrent validity using Pearson’s product moment correlation coefficient. Also, the reaction time by the Multi Choice Reaction timer was correlated with the mobile application. Bland-Altman plots were used to explore the existence of any systematic differences between the measurements. Results: Our results showed very strong correlations between the TUG and TUG-subtraction duration derived from the APDM Mobility Lab system and the mobile application (r =0.96 and 0.95, respectively). For the reaction time, the results showed a moderate correlation between the reaction time derived from the mobile application and the Multi Choice Reaction Timer (r = 0.68). Conclusion: The mobile application, which allows measurement in TUG and TUG dual, is a highly valid tool for TUG duration assessment. However, this application is capable for assess the reaction time with moderate validity for reaction time assessment.